A multidimensional implicit approach to gender stereotypes - Panerati, Sara; Rubini, Monica; Giannella, Valeria A.; Menegatti, Michela; Moscatelli, Silvia (Frontiers in Psychology, 2023)
Research has widely explained gender inequalities in terms of gender stereotypes, according to which women are considered more nurturing, empathic, and emotional but less competent – than men. Recent evidence highlights that especially women are portrayed along multiple dimensions. In this research, we adopted an implicit Semantic Misattribution procedure to detect whether gender stereotypes have a multidimensional structure and are differently attributed to men and women. Results showed that Competence and Dominance-related terms were considered more masculine ones. In contrast, Morality and Physical Attractiveness were attributed to feminine ideograms to a higher and significant extent than masculine ones. Sociability was related to feminine and masculine ideograms almost to the same extent. The gathered evidence provided a multidimensional picture even composed of more judgment dimensions with reference to women highlighting how it can be difficult for them to meet all those multiple expectancies.